Mejoramiento genético. Evaluación en viveros uniformes - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
The 3-stage progeny evaluation program at CIAT tested 2300 new materials distributed as follows: 1st stage (bean evaluation nursery-VEF), 1451 entries; 2nd stage (preliminary trials-EP), 394 entries; and 3rd stage (IBYAN), 210 entries. The following data are included in table form for these 3 uniform nurseries: no. of sets of international nurseries (IBYAN, VEF, and EP) dispatched during 1985 to different countries; distribution of the VEF entries; no. of bean entries in the VEF arranged according to growth habit and seed characteristics; no. of bean entries in each group of VEF/85 arranged according to resistance to diseases (angular leaf spot, anthracnose, and Ascochyta leaf spot); exptl. lines with above-av. yields at 2 sites in Colombia (EP/85); yields of the top IBYAN lines arranged according to color class, seed size, growth habit, and location. A summary of the worldwide results of the IBYAN of the previous year is also included. (CIAT)